Excellence and Its Impact on Tourism Service Applied Study in Mansour Hotel - Baghdad - Hassan Al Baraznji, Amal Kamal (Opción, 2019)
Excellence is one of the main pillars of the success and building of organizations, because the guest touches stability and meets his expected and current needs, and reveals the reason for his brilliance in the field of business and his stay in the world of competition and providing distinct services to society in general, the research included two theoretical topics and the third is practical to show the impact and existence of the relationship between the two variables.